Treatment of Advanced Hepatocellular Carcinoma with Somatostatin Analogues: A Review of the Literature - Hendrik Reynaert (International Journal of Molecular Sciences, 2019)
Hepatocellular carcinoma, one of the most dreaded complications of cirrhosis, is a frequent cancer with high mortality. Early primary liver cancer can be treated by surgery or ablation techniques, but advanced hepatocellular carcinoma remains a challenge for clinicians. Most of these patients have underlying cirrhosis, which complicates or even precludes treatment. Therefore, efficacious treatments without major side effects are welcomed. Initial results of treatment of advanced hepatocellular carcinoma with somatostatin analogues were promising, but subsequent trials have resulted in conflicting outcomes. This might be explained by different patient populations, differences in dosage and type of treatment and differences in somatostatin receptor expression in the tumor or surrounding tissue. It has been shown that the expression of somatostatin receptors in the tumor might be of importance to select patients who could benefit from treatment with somatostatin analogues. Moreover, somatostatin receptor expression in hepatocellular carcinoma has been shown to correlate with recurrence, prognosis, and survival. In this review, we will summarize the available data on treatment of primary liver cancer with somatostatin analogues and analyze the current knowledge of somatostatin receptor expression in hepatocellular carcinoma and its possible clinical impact.